1990
DOI: 10.1099/0022-1317-71-9-1957
|View full text |Cite
|
Sign up to set email alerts
|

Sulphoevernan, a polyanionic polysaccharide, and the narcissus lectin potently inhibit human immunodeficiency virus infection by binding to viral envelope protein

Abstract: Sulphoevernan is a sulphated ~-1 --, 3, 1 -, 4 polyglucan (Mr 20000) with a helical structure. This compound effectively inhibits both human immunodeficiency virus type 1 (HIV-1) and type 2 infection of cells in vitro at concentrations around 0-5 ~tg/ml. Moreover, the compound completely inhibits HIV-l-induced syncytium formation at a concentration of 1 ~tg/ml. Competition experiments with 35S-labelled sulphoevernan revealed that the mannose-specific lectin from Narcissus pseudonarcissus prevented binding of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Except for the glycosylated Asn301 amino acid found in the V3 domain of gp120, no mutations were found in the areas that interact with the (co)receptors. It also explains why the mannose-specific plant lectins are unable to prevent gp120/CD4 binding, but instead inhibit the virus fusion process at a stage that follows binding of the virus to the target cells (Matsui et al, 1990;Weiler et al, 1990). Several investigators have studied the effect of mutations in gp120 on viral infectivity and (co)receptor interaction.…”
Section: Depletion Of Glycosylation Sites In Hiv Gp120 By Plant Lectimentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the glycosylated Asn301 amino acid found in the V3 domain of gp120, no mutations were found in the areas that interact with the (co)receptors. It also explains why the mannose-specific plant lectins are unable to prevent gp120/CD4 binding, but instead inhibit the virus fusion process at a stage that follows binding of the virus to the target cells (Matsui et al, 1990;Weiler et al, 1990). Several investigators have studied the effect of mutations in gp120 on viral infectivity and (co)receptor interaction.…”
Section: Depletion Of Glycosylation Sites In Hiv Gp120 By Plant Lectimentioning
confidence: 99%
“…In addition, they combine specifically with a variety of oligosaccharides composed of these monosaccharides. It has been shown that a number of plant lectins, in particular those with specificity for mannose oligomers, display potent inhibitory activity against several viruses, such as HIV (Lifson et al, 1986;Muller et al, 1988;Matsui et al, 1990;Weiler et al, 1990;Balzarini et al, 1991Balzarini et al, , 1992Animashaun et al, 1993), human cytomegalovirus (HCMV) (Balzarini et al, 1991), and coronaviruses [i.e., feline coronavirus (feline infectious peritonitis virus) and human coronavirus (SARS)] (Balzarini et al, 2004c). Moreover, some of these plant lectins [i.e., Galanthus nivalis agglutinin (GNA) and Hippeastrum hybrid agglutinin (HHA)] were recently demonstrated to represent potential candidate anti-HIV microbicides; they lack mitogenic activity, do not lead to human blood cell agglutination, and show marked stability at relatively low pH and high temperatures for prolonged time periods (Balzarini et al, 2004a).…”
mentioning
confidence: 99%
“…These compounds were found to abolish HIV-1-induced formation of syncytia and to block the adsorption of the virus to the CD4 + target cells (Baba et al, 1988;Biesert et al, 1988). The sulfated polyglucan sulphoevernan, another polyanion displaying anti-HIV-activity in vitro, has been shown to act through binding to the virus (Weiler et al, 1990). Our results revealed that sulfated colominic acid only suppresses PrP Sc and HIV-1 gp120-induced neurotoxicity when preincubated with these toxic agents.…”
Section: Both Prpmentioning
confidence: 61%
“…Previously we reported that the lectin from Gerardia savaglia (GL) (M r 32 000; Kljajic et al, 1987) and the lectin from Narcissus pseudonarcissus (NPL) (M r 25 000; Van Damme et al, 1988), which bind to gp120 with high af®nity , are able to suppress infection of cells with HIV-1 (Weiler et al, 1990;Mu È ller et al, 1988) and gp120-induced neurotoxicity (Mu È ller et al, 1992). As shown in Figure 2, coincubation of gp120 with a 19-fold (GL) or 24-fold (NPL) molar excess of the lectins compared to gp120 almost totally abolished both gp120-induced apoptosis (P50.01; Figure 2A) and cell killing (P50.01; Figure 2B).…”
Section: Figure 3 Neuroprotective Effect Of Sulfated Colominic Acid Omentioning
confidence: 99%
“…In addition, they combine specifically with a variety of oligosaccharides composed of these monosaccharides. It has been shown that a number of plant lectins, in particular those with specificity for mannose oligomers, display potent inhibitory activity against several viruses, including HIV [4,[50][51][52][53][54], human cytomegalovirus (HCMV) [53], and coronaviruses [i.e., feline coronavirus (feline infectious peritonitis virus) and human coronavirus (SARS)]. Such observations suggest that common glycosyl structures on these viruses are ligands for host receptors.…”
Section: Defining Carbohydrate Epitopes Relevant As Vaccine Targetsmentioning
confidence: 99%